2010
DOI: 10.1089/fpd.2009.0372
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Genes Controlled byluxS/Autoinducer-2 inSalmonella entericaSerovar Typhimurium

Abstract: The enteric pathogen Salmonella enterica serovar Typhimurium uses autoinducer-2 (AI-2) as a signaling molecule. AI-2 requires the luxS gene for its synthesis. The regulation of global gene expression in Salmonella Typhimurium by luxS=AI-2 is currently not known; therefore, the focus of this study was to elucidate the global gene expression patterns in Salmonella Typhimurium as regulated by luxS=AI-2. The genes controlled by luxS=AI-2 were identified using microarrays with RNA samples from wild-type (WT) Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 41 publications
(56 reference statements)
1
46
0
Order By: Relevance
“…The Lsr transport system is well-known to be involved in the detection and transport of AI-2 into the cell, while the rbs transporter has recently been suggested as an alternative AI-2 uptake system (Jesudhasan et al, 2010). A number of research groups reported that Salmonella biofilm formation is affected by mutating the luxS gene.…”
Section: Role Of Quorum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lsr transport system is well-known to be involved in the detection and transport of AI-2 into the cell, while the rbs transporter has recently been suggested as an alternative AI-2 uptake system (Jesudhasan et al, 2010). A number of research groups reported that Salmonella biofilm formation is affected by mutating the luxS gene.…”
Section: Role Of Quorum Sensingmentioning
confidence: 99%
“…Prouty et al found that a S. Typhimurium luxS insertion mutant only showed scattered biofilm formation with little apparent EPS on the surface of gallstones after 4 days of incubation (Prouty et al, 2002). Jesudhasan et al reported that a S. Typhimurium luxS deletion mutant is impaired in biofilm formation on polystyrene (Jesudhasan et al, 2010). Microarray analysis revealed that several motility genes and biofilm-related genes are down-regulated in the luxS deletion mutant as compared to the wildtype.…”
Section: Role Of Quorum Sensingmentioning
confidence: 99%
“…Much research interest on biofilm formation by Salmonella has been focused on confirming the regulatory genes (Jesudhasan et al, 2010). White, Gibson, Kim, Kay, and Surette (2006) have found that thin aggregative fimbriae and cellulose (agfD and agfA) enhance long-term survival and persistence of Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…The second QS system of Salmonella uses the LuxS enzyme for the synthesis of AI-2 (Schauder et al, 2001;Soni et al, 2008). The Lsr ABC transporter is known to be involved in the detection and transport of AI-2 into the cell (Taga et al, 2001), while the rbs transporter has recently been suggested as an alternative AI-2 uptake system (Jesudhasan et al, 2010). A S. Typhimurium luxS deletion mutant was impaired in biofilm formation on polystyrene (De Keersmaecker et al, 2005;Jesudhasan et al, 2010).…”
Section: Cell-to-cell Communication In Salmonella Biofilms (Quorum Sementioning
confidence: 99%
“…The Lsr ABC transporter is known to be involved in the detection and transport of AI-2 into the cell (Taga et al, 2001), while the rbs transporter has recently been suggested as an alternative AI-2 uptake system (Jesudhasan et al, 2010). A S. Typhimurium luxS deletion mutant was impaired in biofilm formation on polystyrene (De Keersmaecker et al, 2005;Jesudhasan et al, 2010). However, this phenotype could not be complemented by extracellular addition of QS signal molecules, suggesting that AI-2 is not the actual signal involved in Salmonella biofilm formation (De Keersmaecker et al, 2005).…”
Section: Cell-to-cell Communication In Salmonella Biofilms (Quorum Sementioning
confidence: 99%